Genetic stratification of motor and QoL outcomes in Parkinson's disease in the EARLYSTIM study. (October 2022) - Weiss, Daniel; Landoulsi, Zied; May, Patrick; Sharma, Manu; Schüpbach, Michael; You, Hana; Corvol, Jean Christophe; Paschen, Steffen; Helmers, Ann-Kristin; Barbe, Michael; Fink, Gereon; Kühn, Andrea A.; et al.
Abstract: Purpose: The decision for subthalamic deep brain stimulation (STN-DBS) in Parkinson's disease (PD) relies on clinical predictors. Whether genetic variables could predict favourable or unfavourable decisions is under investigation. Objective: First, we aimed to reproduce the previous observation that SNCA rs356220 was associated with favourable STN-DBS motor response. In additional exploratory analyses, we studied if other PD risk and progression variants from the latest GWAS are associated with therapeutic outcome. Further, we evaluated the predictive value of polygenic risk scores. Methods: We comprehensively genotyped patients from the EarlyStim cohort using NeuroChip, and assessed the clinico-genetic associations with longitudinal outcome parameters. Results: The SNCA rs356220 variant did not predict UPDRS III outcomes. However, it was associated with quality of life improvement in secondary analyses. Several polymorphisms from previously identified GWAS hits predicted motor or quality of life outcomes in DBS patients. Polygenic risk scores did not predict any outcome parameter. Conclusions: Our findings support the hypothesis that different common genetic markers are associated with favourable quality of life outcomes of STN-DBS in PD. These findings can be the basis for further validation in larger and independent cohorts. Highlights: SNCA rs356220 did not predict UPDRS III in STN-DBS group of PD patients. SNCA rs356220 was associated with quality-of-life improvement. Different SNPs from PD GWAS hits predicted motor or PDQ-39 outcomes. Further validation in larger cohorts is needed to confirm these findings